EVALUATING ENGINEERING GRAPHICS AND DESIGN EDUCATION: CONTEXTUAL FACTORS, INSTRUCTIONAL PRACTICES, AND TECHNOLOGY BARRIERS - Masingi, Jamela; Khoza, Samuel (Education Administration Study Program, School of Postgraduate Studies, Universitas Riau, 2024)
The purpose of this qualitative study was to evaluate the contextual factors that impede the integration of technology in Engineering Graphics and Design (EGD) teaching in selected schools of the Limpopo province. The interpretive paradigm was used to understand the data from the participants of this case study. The Technological Pedagogical Content Knowledge was used as an underpinning theoretical framework for the study. The population of interest included five technical schools of the same quintile where two teachers from each school were purposefully selected. A purposive sample was used to select 10 teachers to take part in the study. The classroom observations showed that not all teachers have digital tools in their classrooms and that some learners have more advanced EGD software than the ones that the teachers have. Teachers also mentioned that they only use WhatsApp as a communication application to provide notifications to learners. The recommendations are that the Department of Education should assist schools in procuring relevant and advanced digital tools and utilizing technology for EGD subjects. To address this, the Department of Education should invest money and provide workshops on technology integration, to train the teachers about gadgets, and how to use them. Regular monitoring of the digital tools will ensure their daily use in the EGD classes.